Na(+)–K(+) pump stimulation restores carbacholine-induced loss of excitability and contractility in rat skeletal muscle - Macdonald, WA (Blackwell Science Inc, 2005)
Intense exercise results in increases in intracellular Na(+) and extracellular K(+) concentrations, leading to depolarization and a loss of muscle excitability and contractility. Here, we use carbacholine to chronically activate the nicotinic acetylcholine (nACh) receptors to mimic the changes in membrane permeability, chemical Na(+) and K(+) gradients and membrane potential observed during intense exercise. Intact rat soleus muscles were mounted on force transducers and stimulated electrically to evoke short tetani at regular intervals. Carbacholine produced a 2.6-fold increase in Na(+) influx that was tetrodotoxin (TTX) insensitive, but abolished by tubocurarine, resulting in a significant 36% increase in intracellular Na(+), and 8% decrease in intracellular K(+) content. The mid region, near the motor end plate, had much larger alterations than the more distal regions of the muscle, and showed a larger membrane depolarization from −73 ± 1 to −60 ± 1 mV compared with −64 ± 1 mV. Carbacholine (10(−4)m) significantly reduced tetanic force to 31 ± 3% of controls, which underwent significant recovery upon application of Na(+)–K(+) pump stimulators: salbutamol (10(−5)m), adrenaline (10(−5)m) and calcitonin gene-related peptide (CGRP; 10(−7)m). The force recovery with salbutamol was accompanied by a recovery of intracellular Na(+) and K(+) contents, and a small but significant 4–5 mV recovery of membrane potential. Similar results were obtained using succinylcholine (10(−4)m), indicating that Na(+)–K(+) pump stimulation may prevent or restore succinylcholine-induced hyperkalaemia. The stimulation of the Na(+)–K(+) pump allows muscle to partially recover contractility by regaining excitability through electrogenically driven repolarization of the muscle membrane.